Effects of Cognitive Behavioral Therapy for Insomnia on Sleep, Symptoms, Stress, and Autonomic Function Among Patients With Heart Failure. Issue 2 (3rd March 2020) - Redeker, Nancy S.; Conley, Samantha; Anderson, George; Cline, John; Andrews, Laura; Mohsenin, Vahid; Jacoby, Daniel; Jeon, Sangchoon
ABSTRACT: Background : Insomnia is common among patients with stable heart failure (HF) and associated with inflammation and altered autonomic function. Purpose : The purposes of this study were to examine the effects of cognitive behavioral therapy for insomnia (CBT-I) on the Hypothalamic Pituitary (HPA) Axis, autonomic function, inflammation, and circadian rhythmicity and the associations between these biomarkers and insomnia, sleep characteristics, symptoms, functional performance, and sleep-related cognitions. Methods : We conducted a subanalysis of a pilot randomized controlled trial (RCT, NCT02827799) whose primary aim was to test the effects of CBT-I on insomnia. We randomized 51 patients with stable Class II-IV HF to CBT-I ( n = 30) or attention control ( n = 21). Participants completed wrist actigraphy and self-reported insomnia severity, sleep characteristics, sleep-related cognitions, daytime symptoms, and functional performance. We measured day and nighttime urinary free cortisol, melatonin sulfate, epinephrine, and norepinephrine at baseline, and two weeks after CBT-I and computed general linear models and partial correlations. Results : CBT-I had no effects on the biomarkers, but there were statistically significant negative cross-sectional correlations between the ratio of day and night urinary free cortisol and sleep disturbance, anxiety, fatigue, depression, and negative sleep cognitions. Increases in the ratio between day and night cortisol were associated with statistically significant improvements in fatigue, depression, sleep duration, and sleep-related cognitions. Conclusions : Biomarkers of stress and autonomic function are associated with sleep, sleep-related symptoms, and cognitions among people with chronic HF. Future studies are needed to identify potential causal relationships and the impact of sleep interventions.